Effect of a combination of pea protein, grape seed extract and lactic acid in an in vivo model of bacterial vaginosis - Lanza, Marika; Scuderi, Sarah Adriana; Capra, Anna Paola; Casili, Giovanna; Filippone, Alessia; Campolo, Michela; Cuzzocrea, Salvatore; Esposito, Emanuela; Paterniti, Irene (Scientific reports, 2023)
Bacterial vaginosis (BV) is a common vaginal dysbiosis characterized by a malodorous discharge and irritation. The imbalance of the vaginal microbiota plays a key role in the development of BV . It has been demonstrated that Gardnerella vaginalis (GV), a facultative anaerobic bacillus, is involved in BV. Due to the rising number of antimicrobial-resistant species, recurrence of BV is becoming more frequent in women; thus, alternative treatments to antibiotics are needed. Natural substances have recently shown a great efficacy for the treatment of vaginal dysbiosis. Thus, this study aimed to investigate the beneficial effect of a product containing pea protein (PP), grape seed extract (GS) and lactic acid (LA) in an in vivo model of Gardnerella vaginalis-induced vaginosis by intravaginal administration of GV suspension (1 × 10 6 CFU/20 µL saline). Our results demonstrated that the product containing PP, GS and LA significantly reduced GV proliferation. More specifically, it significantly preserved tissue architecture and reduced neutrophil infiltration, inflammatory markers and sialidase activity when used both as a pre- or a post-treatment. Moreover, the product displayed strong bioadhesive properties. Therefore, our data suggested that the product containing PP, GS and LA could be used as alternative preventive or curative treatment for the management of BV.